Selection of Compronents for Tracking Systems of A Solar Plant - Sultonov Shuxrat Davlyatovich; Tojiboyev Abror Kahorovich (Zien Journals, 2022)
The article presents a methodology for selecting electrical and mechanical components of solar installation tracking systems to improve the overall efficiency of a solar installation.
Keywords: tracking system; component; controller; research